LEVEL OF LEARNING DISCIPLINE STUDENTS CLASS IX SMP NEGERI 6 PURWODADI - Nur Rini Wulanjari (Yayasan Citra Dharma Cindekia, 2022)
Formula in this research is how the level of discipline in class IX students of SMP Negeri 6 Purwodadi; This research is an expost facto quantitative research with a sample of 45 students. The study began with initial interviews with the principal and homeroom teacher of class IX at SMP Negeri 6 Purwodadi, namely Agus Prasetyo. The results of interviews and initial observations were used as supporting data and preparation of the background and formulation of the problem. The research implementation (data collection) will be held on May 31, 2021. Data collection techniques in this study were through questionnaires and documentation. Before conducting the data analysis, a prerequisite test for data analysis was carried out that had met the requirements both in the normality test and linearity test. The results showed that there were various levels of student learning discipline.